2017
DOI: 10.1007/s00114-016-1429-1
|View full text |Cite
|
Sign up to set email alerts
|

Do horses with poor welfare show ‘pessimistic’ cognitive biases?

Abstract: This field study tested the hypothesis that domestic horses living under putatively challenging-to-welfare conditions (for example involving social, spatial, feeding constraints) would present signs of poor welfare and co-occurring pessimistic judgement biases. Our subjects were 34 horses who had been housed for over 3 years in either restricted riding school situations (e.g. kept in single boxes, with limited roughage, ridden by inexperienced riders; N = 25) or under more naturalistic conditions (e.g. access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 107 publications
2
51
0
2
Order By: Relevance
“…In horses, backward ear position is commonly associated with negative emotional states, such as pain or a negative cognitive bias [ 34 , 67 , 68 ]; or during agonistic interactions [ 69 ]. Ear position for each horse was noted at 15 minute intervals and on two different rest days until 10 ear positions were obtained per horse according to the method used by Lesimple et al [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…In horses, backward ear position is commonly associated with negative emotional states, such as pain or a negative cognitive bias [ 34 , 67 , 68 ]; or during agonistic interactions [ 69 ]. Ear position for each horse was noted at 15 minute intervals and on two different rest days until 10 ear positions were obtained per horse according to the method used by Lesimple et al [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, chronic health disorders are related to typical postures, such as laminitis with an arched body that takes the weight off the fore feet [20]. Ear positions are good indicators: if ears pointing backwards are associated with negative states, including pain (e.g., [20] for a review) or agonistic social interactions [70], they are also associated with chronically restricted conditions-the time spent with ears backwards in homogenous conditions (i.e., foraging) is related to chronically restricted living conditions (strict social isolation [35]) and chronic welfare impairment (e.g., vertebral disorders, stereotypic behaviours [36,37]), while horses under naturalistic conditions are almost never observed with such ear positions. Although time spent with ears backwards while foraging is not related to one particular context, it is a reliable indication of impaired welfare.…”
Section: Postural Indicatorsmentioning
confidence: 99%
“…Finally, a cognitive bias was shown to reflect horses' welfare state. Thus, a recent study [37] showed that horses in a poor welfare state (evaluation based on the expression of SB/ARB, ear position, aggressive reactions to humans and vertebral disorders) were also more pessimistic when in the presence of an ambiguous stimulus, whereas horses in a good welfare state were clearly optimistic.…”
Section: Other Behavioural Indicatorsmentioning
confidence: 99%
“…Some new or better-defined indicators may be worth investigating: "alertness", "attentional engagement" and "responsiveness" are a strong part of the SEBWAT protocol and have revealed interesting [29,39,43], as well as some acoustic signals (e.g., [75]), and would deserve refining. Ear positions during feeding on roughage or grass correlate with cognitive biases, and hence represent horses' perception of their situation [76] and this criterion is under validation. Burn et al [29] identified positive reactions to human approaches as a sign of good welfare.…”
Section: Welfare Indicatorsmentioning
confidence: 99%